2018
DOI: 10.3390/brainsci8080144
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Structural Magnetic Resonance Imaging in Differentiating Chronic Disorders of Consciousness

Abstract: Differential diagnosis of unresponsive wakefulness syndrome (UWS) and minimally conscious state (MCS) is one of the most challenging problems for specialists who deal with chronic disorders of consciousness (DOC). The aim of the current study was to develop a conventional MRI-based scale and to evaluate its role in distinguishing chronic disorders of consciousness (Disorders of Consciousness MRI-based Distinguishing Scale, DOC-MRIDS). Data were acquired from 30 patients with clinically diagnosed chronic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…A growing number of studies have also demonstrated a critical role of thalamo-cortical connections ( Maxwell et al, 2004 , Fernández-Espejo et al, 2011 ) within the fronto-parietal ( Long et al, 2016 , Crone et al, 2014 ) and default mode brain networks ( Fernández-Espejo et al, 2012 , Vanhaudenhuyse et al, 2009 ) in the sustenance of awareness. Our findings also align with the study of Morozova et al (2018 )., who developed a diagnostic MRI scoring system differentiating between the chronic UWS and MCS patients based on brain atrophy. The chronic UWS was marked by a degeneration of the brainstem and thalamus, widespread diffuse cortical atrophy, and degeneration of the corpus callosum, pointing to the importance of the preserved integrity of these brain regions in the sustenance of consciousness.…”
Section: Discussionsupporting
confidence: 93%
“…A growing number of studies have also demonstrated a critical role of thalamo-cortical connections ( Maxwell et al, 2004 , Fernández-Espejo et al, 2011 ) within the fronto-parietal ( Long et al, 2016 , Crone et al, 2014 ) and default mode brain networks ( Fernández-Espejo et al, 2012 , Vanhaudenhuyse et al, 2009 ) in the sustenance of awareness. Our findings also align with the study of Morozova et al (2018 )., who developed a diagnostic MRI scoring system differentiating between the chronic UWS and MCS patients based on brain atrophy. The chronic UWS was marked by a degeneration of the brainstem and thalamus, widespread diffuse cortical atrophy, and degeneration of the corpus callosum, pointing to the importance of the preserved integrity of these brain regions in the sustenance of consciousness.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our structural analyses show a significant atrophy for both patient groups in subcortical structures such as the thalamus, which was also previously found to be damaged in MCS patients. 24,25 In comparison with the group of MCS− patients, MCS+ patients presented higher metabolism preservation in different language-related areas. Using a more conservative correction (ie, FWE), higher metabolism was identified in MCS+ compared with MCS− in the left middle temporal cortex, which has been associated to selective processing of speech, 26,27 semantic processing, 28,29 and word generation.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, our structural analyses show a significant atrophy for both patient groups in subcortical structures such as the thalamus, which was also previously found to be damaged in MCS patients. 24,25…”
Section: Discussionmentioning
confidence: 99%
“…Another feasible explanation is that the reduction of the serum BDNF level is caused by the loss of BDNF-secreting neurons as a consequence of acute brain injury and subsequent brain atrophy. Neuroimaging studies have shown that patients with DOCs develop widespread cortical and subcortical atrophy [38][39][40]. Moreover, the degree to which markers of neuronal injury, such as neuron-specific enolase, are released is below normal in the chronic phases of DOCs [41], suggesting the progressive loss of neurons with brain atrophy [42].…”
Section: Discussionmentioning
confidence: 99%